Factors Influencing the Emergence of Hate Speech in the Handling of Land Conflicts in North Sumatra - Lubis, Afifi; Sazali, Hasan; Ritonga, Hasnun Jauhari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the factors that influence the emergence of hate speech in handling land conflicts in North Sumatra. This study uses a qualitative method with a case study approach. The data for this study are sourced from observations, interviews, and literature reviews. The data for this study were analyzed through data reduction, data presentation, and drawing conclusions. The validity of the research data was determined through triangulation techniques. This study shows that land conflicts in North Sumatra, especially in the former HGU PTPN II land since 2002, were triggered by unclear land regulations, legal uncertainty, and high economic value, which exacerbated social tensions and hate speech. Competition between local communities, large companies, and local governments is heating up due to the spread of unverified information on social media and the slow response of the government, which has led to public distrust. Additional factors such as imbalance of power, socio-cultural differences, and lack of communication education and uncontrolled use of technology exacerbate the conflict. Proposed solutions include clear land regulations, effective communication strategies with neutral mediators, government transparency, judicious use of social media, and training of mediators and empowerment of local communities to strengthen social cohesion and achieve inclusive and sustainable conflict resolution.